Effect of revegetation and of fertilization of degraded area on soil fertility and on characteristics of straw mulch - Favaretto, Nerilde; Moraes, Aníbal de; Motta, Antônio Carlos Varga; Prevedello, Beatriz Monte Serrat (Pesquisa Agropecuaria Brasileira, 2000)
This work was carried out on a soil degraded by oil shale mining in São Mateus do Sul, PR, Brazil, to determine the soil fertility and the characteristics of straw mulch after revegetation with forage species submitted to different fertilizations. The experimental design was setup in randomized blocks with split plots, being three plots concerning fertilizations and three subplots with forage species. The fertilizations used were: I - mineral fertilizer with aerial part left over; II - mineral and organic fertilizer with aerial part excluded; III - mineral fertilizer with aerial part excluded. The forages established different systems: Systems I and II - perennial grasses and legumes species of winter and summer; System III - annual grasses and legumes species of winter and summer. The soil chemical properties were determined in the 0-3 and 3-9 cm depths. Percentage of soil covered, weight of residual dry matter, C and N concentrations and the amount of these nutrients were also analyzed. The treatments changed the chemical properties of the soil, mainly in 0-3 cm depth, and in general, better results were obtained with organic fertilization. Considering that the content of organic matter is the main factor on reclamation process, the perennial species were more adequate, however, all forage systems shown high percentage of soil covered.